A guerra tributária intermunicipal: uma análise sobre os efeitos da política de harmonização tributária sobre o fenômeno da arrecadação dos municípios da região metropolitana de São Paulo - Oliveira, Euripedes Magalhães de (2010)
The purpose of this study is to assess the adoption of EC n ° 37, from June 12, 2002, covered by LC 116, on July 31, 2003, as a means to contain the tax war among municipalities. Thus, it aims to assess the impacts of the adoption of a rate floor for ISSQN on the tax collection of cities, taking the cities that comprise the MRSP as the main object of analysis. The importance of this issue is identified in the relationship among federal entities, the discussion of tax and financial autonomy in the Brazilian federation and how these issues impact the provision of public goods. This work uses a simple model designed to understand the tax collection via ISSQN and seeks to infer the results caused by the adoption of an external measure of harmonization of tax rates. Positive and significant results were found in this study. It is hoped that this work will contribute with new perspectives of studies in the area of fiscal federalism, especially for studies about local governments in Brazil. At the same time, it is hoped to contribute to the development of researches on the tax rates, tax revenues, the tax model and national discussions on allocation of powers between the federal entities.